Effect of clinician’s experience and expertise on the inter- and intra-observer reliability of the computed tomography-based classification systems in posterior malleolus fractures - Yiğit Umur Cırdı; Mehmet Demirel; Mahmut Enes Kayaalp; Ramazan İlter Öztürk; Muhammet Bozoğlan; Andrea Giordano Salvi (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: Three computed tomography (CT)-based classifications, including Haraguchi, Bartoníček–Rammelt, and Mason–Molloy systems, have been developed to better determine the characteristics of posterior malleolus fractures (PMFs). The aims of this study were (1) to determine the intra- and inter-observer reliability of the computed tomography-based classification systems and (2) to investigate the clinical experience and expertise on their reliabilities.